Energy Price Formation and Energy Consumption by Households as a Factor of Ensuring Energy Safety - Prasolov, Valeriy; Bezpalov, Valery; Doguchaeva, Svetlana; Rogulin, Rodion (International Journal of Energy Economics and Policy, 2020)
The objective of the article was to analyze the issue of developing energy price formation by various countries in the context of component structure of the cost per energy unit for households. For conducting the research the principles “Expenses +” and Regulatory Asset Base were used. A methodological author's approach related to the estimation of pricing level for energy resources based on Energy Pricing Index was proposed. The highest gas prices are in Sweden, Denmark, Portugal, France and Ireland that relates not so much to gas market as to the prime cost of green electricity. The specific feature of the price policy in European countries is the establishment of higher gas prices for households than for industries. Unlike Russia, “cross-subsidization” has completely opposite content. The value of gas price in European countries does not depend on whether this country is its producer on its territory. However, there is an inverse relation between the production level of energy resources and the level of economic development. In view of the low EPI based on overestimate network costs and actual lack of the components' differentiation of the fixed price, the low level of pricing efficiency is observed in Moldova, Ukraine and Serbia. Keywords: energy resource; green electricity; price formation; rent; sustainable development. JEL Classifications: O13, P28, Q4. DOI: https://doi.org/10.32479/ijeep.9666